PENGARUH IKLAN LIPTINT IMPLORA TERHADAP SIKAP KONSUMEN SERTA TINGKAT KEPUASAN PEMBELIAN PADA REMAJA: Survei pada Mahasiswa S1 Universitas Negeri Surabaya dalam Peniliaian Kepuasan Produk Liptint Implora - Enggar, Amanda; Agustina, Anisa; Yeshaya, Talitha (Journal of Beauty and Cosmetology (JBC), 2024)
This study aims to examine the effect of advertising on consumer attitudes and the level of purchase satisfaction of adolescents. This study uses a type of quantitative research. The data collection method was carried out by distributing questionnaires to 24 respondents, namely S1 students at Surabaya State University. The sampling technique used was purposive sampling. Data analysis used is descriptive analysis. Based on the results of the study, it can be concluded that the better the advertising on social media, the more positive attitudes consumers will give which can ultimately lead to purchasing decisions. For consumers, price is often used. There were population criteria taken in this study, namely female students at Surabaya State University who had made a purchase transaction, used Implora Liptint products, and had also seen Implora advertisements on social media. Keywords : Advertisement, Consumer Attitude, Purchase Decicion